La prospection archéologique - Ferdière, Alain; Zadora-Rio, Elisabeth (Éditions de la Maison des sciences de l’homme, 2022)
This third D.A.F. volume publishes papers presented at the symposium on landscape archaeology, organised in 1982 by A. Ferdière and E. Zadora-Rio. Fieldwork and landscape studies have today entered more than ever into present archaeological thinking. Such studies are not now limited just to evidence from excavated sites, but to the surrounding natural and human environment, permitting the reconstruction of earlier landscapes. Fieldwork, now established as a discipline in its own right, enables the relationship between actual sites and exploitation sequences of their associated landscape to be better understood. Taking into account the theoretical and practical impossibilities of total fieldwork, speakers at this symposium, in both their communications and during discussions, presented different choices of objectives and methods, and analysed the strengths and weaknesses of each technique adopted.